The Urgency Of Digital Business In Improving The Rural Community Youth Organization's Business - Amruddin, Amruddin; Safari, Apay; Masita, Ella; Indrawati, R.A.; Utami, Eva Yuniarti (Journal Of Human And Education (JAHE), 2024)
When researchers carried out service to Karang Tarruna, Baji Mappakasunggu Village, Makassar, Indonesia, Ciumbuleuit Village, Bandung, Kerinci Village, Jambi, Amali Village, Bone Regency, and Serengan Village, Surakarta. Researchers found a problem that Karang Taruna in the five villages did not have a source of income so that when carrying out activities, they were too dependent on funds owned by the village government. As a result, the resulting work program does not have significant implications for achieving the desired goals. After discussion, the writer and servant have a solution for Kaarang Taruna to have a digital business/digital-based MSME with the following urgency and reasons: 1). Digital Business/Digital-based MSMEs have several urgencies, namely that Karang Taruna can not depend on the village government, can produce activities that are of higher quality and have a more significant impact, and the Karang Taruna and young people empowerment program can run and the quality always increases . 2). Digital Business/Digital MSMEs is the most suitable and appropriate business model because you don't have to have a lot of capital, don't have rental costs, and marketing can be done in a quicker and shorter time.